The Relationship Between Teacher Support and Student Motivation with Adherence to Comsumption of Blood Suplementary Tablets in Female Students at Smp Negeri 2 Muara Kaman Year 2023 - Maya Dewi Fronika; Andi Parellangi; Nursari Abdul Syukur; Nilam Noorma (International Journal of Scientific Multidisciplinary Research, 2023)
Anemia is a condition where the level of hemoglobin (Hb) in the blood is less than normal. Young women are prone to anemia because they experience menstrual periods and catch up on growth. Preliminary studies on female students of SMP Negeri 2 Muara Kaman found that there were those who did not consume Blood Supplement Tablets given by the teacher. The aim is to determine the relationship between teacher support and student motivation with adherence to consumption of Blood Supplementary Tablets in female students. This type of research is analytic observation using a cross sectional design. The population is 198 students at SMP Negeri 2 Muara Kaman, using the Lemeshow formula, a sample of 84 people is obtained. The sampling technique uses simple random sampling. Data analysis using Chi-Square. The characteristics of the respondents were mostly 13-year-old students (48.8%), parents had graduated from high school (41.7%) and their parents worked as private employees (40.5%). Most of the teacher's support was not good (51.2%), the motivation of the students was mostly moderate/weak (48.8%) and they were not compliant with consuming iron supplement tablets (54.8%)